PROTOCOL: Factors influencing the implementation of non-pharmacological interventions for behaviours and psychological symptoms of dementia in residential aged care homes: A systematic review and qualitative evidence synthesis - Ayeno, Hunduma Dinsa; Kassie, Gizat M; Atee, Mustafa; Nguyen, Tuan Anh (Wiley Open Access, 2024)
This is a protocol for a Cochrane Review. The objectives are as follows. This paper aims to describe a protocol for a systematic review that will synthesise the qualitative evidence regarding factors influencing the implementation of non-pharmacological interventions (NPIs) for behavioural and psychological symptoms of dementia (BPSD) management in residential aged care homes (RACHs). The planned systematic review aims to answer the research question: ‘What are the factors influencing the implementation of NPIs in the management of BPSD at RACHs?’. Additionally, the planned systematic review also aims to generate recommendations to guide stakeholders (e.g., clinicians and aged care staff) and policymakers in the implementation of NPIs for managing BPSD at RACHs.